Pseudostate description of diatomic-molecule scattering from a hard-wall potential - Lugovskoy, Andrey; Bray, Igor (American Physical Society, 2013)
A collinear scattering of a structured particle from a hard wall is studied with consideration of vibrational transitions initiated by the collision. It is shown that this problem can be solved analytically in the framework of the source-function method. With the use of the continuum discretization technique we are able to take into account both discrete and continuum states. No approximations of the interatomic potential is required. We illustrate our approach for the case of a hydrogen molecule bound by the realistic Morse potential.